2021
DOI: 10.1029/2020gl091332
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reduction of pH and CaCO3 Saturation State in the Tsugaru Strait by the Intensified Tsugaru Warm Current During 2012–2019

Abstract: Ocean absorption of the CO 2 released to the atmosphere by human activities (i.e., anthropogenic CO 2 ) results in acidification of surface waters as the result of the increase in hydrogen ion (H + ) concentration. The oceanic uptake of anthropogenic CO 2 has decreased ocean pH by 0.1 since the beginning of the industrial era (Intergovernmental Panel on Climate Change, 2013). Ocean acidification also lowers the CaCO 3 saturation state (Ω) by decreasing carbonate ion (CO 3 2− ) concentration with concomitant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The outflow from the channel encounters low temperature and salinity water described as the coastal Oyashio water by the previous studies (e.g., Kono et al, 2004;Rosa et al, 2007;Saitoh et al, 2008;Kuroda et al 2012;Wakita et al, 2021) in the outlet of the eastern neck of the channel (~141.2°E; Fig. 1b).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The outflow from the channel encounters low temperature and salinity water described as the coastal Oyashio water by the previous studies (e.g., Kono et al, 2004;Rosa et al, 2007;Saitoh et al, 2008;Kuroda et al 2012;Wakita et al, 2021) in the outlet of the eastern neck of the channel (~141.2°E; Fig. 1b).…”
Section: Introductionmentioning
confidence: 67%
“…In the Tsugaru Strait, recent studies reported significant disturbance due to the intense flow and tides (e.g., Yamaguchi et al, 2020;Tanaka et al, 2021), and subsequent characteristic change in ocean environment there (Wakita et al, 2021). Yamaguchi et al (2020) suggested generation of internal waves that have large-amplitude in the vertical direction behind a characteristic topography (sill) in the western part of the strait based on observations and numerical experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seawater samples were collected when the sensors were calibrated and analyzed using a total alkalinity (TA) titration analyzer (ATT-05; Kimoto Electric) to obtain the TA and a coulometer (MODEL 3000A; Nippon ANS) to determine the dissolved inorganic carbon (DIC) concentration (Wakita et al, 2017(Wakita et al, , 2021Yamaka, 2019). The values were calibrated against certified reference material (CRM) provided by Prof. A. G. Dickson (Scripps Institution of Oceanography, University of California San Diego) and KANSO.…”
Section: Monitoringmentioning
confidence: 99%
“…Therefore, it is likely that we failed to capture the annual minimum value of arag in this study. However, referring to observed seasonal fluctuations in arag (e.g., Ishii et al, 2011;Wakita et al, 2017Wakita et al, , 2021, the annual minimum should appear in winter when the water temperature is low and the value may have already reached close to the critical level of acidification.…”
Section: Biogeochemical Parametersmentioning
confidence: 99%